INDEKS NILAI KEBERLANJUTAN ASPEK EKONOMI PADA HUTAN RAKYAT POLA AGROFORESTRY DI KABUPATEN KERINCI - Nurmansah, Rahmad; Fazriyas, Fazriyas; Ahyauddin, Ahyauddin; R.P Napitupulu , Richard; Kurnia, Agung (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
Community forests managed under agroforestry systems in Kerinci Regency play a crucial role in enhancing local economic resilience while contributing to ecological balance. However, the long-term economic viability of these systems requires comprehensive assessment to support sustainable development planning. This study aims to evaluate the economic sustainability of agroforestry-based community forests by calculating a sustainability index and identifying the main contributing factors.  A quantitative approach was applied using the Multidimensional Scaling (MDS) method to construct the economic sustainability index. Primary data were collected through structured surveys involving local agroforestry farmers. The results obtained from the analysis of the Sustainability of Community Forests in Kerinci Regency in Community Economic Aspects were obtained with an economic dimension value of 83.08 (Sustainable) with a sustainability status in the economic aspects of community forests. Agroforestry pattern. In conclusion, the management of community forests through agroforestry in Kerinci Regency demonstrates moderate economic sustainability. Efforts to enhance farmer income and improve market access are essential to achieving higher levels of sustainability in the future. In conclusion, the current economic management of community forests in Kerinci through agroforestry demonstrates a fair level of sustainability.